Os processos formativos do investigador da Polícia Civil de Minas Gerais - Letícia Domingos Sena (2020)
The career of Civil Police Investigator of the State of Minas Gerais (PCMG), has changed with the requirement of a minimum graduation level for the admission. New training processes have been added to the old practices of police culture in order to guarantee the diversity of multidisciplinary functions foreseen for the position. In this work we direct our attention to the speeches that circulate about the "good cop" in documentation generated with diverse purposes in the Civil Police Academy of Minas Gerais (Acadepol) such as: legislation, norms, course projects, National Curricular Matrix and the Study of Professional Profile and Competency Mapping (National Secretariat of Public Security). We approached the post-critical conceptions of curriculum, the concepts of police and the Foucaultian assumptions in order to understand the curriculum and interrogate the emergence of discursive formations about the "good cop", the positions of subjects and practices triggered by the functioning of these discourses and the conditions of certain truth effects that circulate in these power-know relationships. We carried out a qualitative documental research, starting from the Content Analysis methodology for the selection of sources and constitution of the corpus. The results demonstrate tensions and disputes that pass through these curricula in an exhaustive and constant search for the ordering of conduct constituting subject positions relative to the good policeman, determining what should be rejected or excluded and allowing different versions of Police Investigator given the multiplicity of possibilities the Investigator's work. The different discursive formations emerge from recurring precepts of hierarchy and discipline, assessments that determine aptitude or not, demand for adaptable profiles, practices consistent with the valorization of legalized violence and the fight against crime, discreet disputes over space for sabers aimed at policing philosophies community conflict and other mediation practices. The good policeman stands out with the efficient, professional, always ready to act and able to use force and legalized violence to fight crime. In this sense, they articulate, come into conflict and compete for space in these curricula, acting in the constitution of what is desirable for a good policeman from the beginning of his career to continuing training.